1990
DOI: 10.1007/bf01974690
|View full text |Cite
|
Sign up to set email alerts
|

Effects of calcium channel blockers on the development of early rat postimplantation embryos in culture

Abstract: Rat embryos (9.5-day-old) were cultured for 48 h in the presence of nifedipine (NIF), nimodipine (NIM), nitrendipine (NIT), gallopamil HCl (GAL), verapamil HCl (VER) and diltiazem HCl (DIL). The effects on growth and morphogenetic differentiation in vitro were monitored. Dose-response relationships were evaluated, including an assessment of the "no-observed-effect-level" (NOEL) or the "lowest-observed-effect-level" (LOEL), and the lowest concentration tested inducing abnormalities in 100% of the embryos ("100%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0
1

Year Published

1994
1994
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 30 publications
(21 reference statements)
1
10
0
1
Order By: Relevance
“…Cultured mouse embryos exposed to L-type channel blockade at later stages than we addressed here, embryonic day 7.5 and older, displayed abnormal cardiac looping, gene expression, and organ development that may relate to effects also on later differentiation, possibly of the second heart field, as well as heart function [23,24]. Similarly, Ca channel blockers also were shown in cultured postimplantation rat embryos to induce morphological anomalies of the heart, head, neural tube, and forelimb [25].…”
Section: Calcium and Cardiac Precursor Cell Differentiationmentioning
confidence: 59%
“…Cultured mouse embryos exposed to L-type channel blockade at later stages than we addressed here, embryonic day 7.5 and older, displayed abnormal cardiac looping, gene expression, and organ development that may relate to effects also on later differentiation, possibly of the second heart field, as well as heart function [23,24]. Similarly, Ca channel blockers also were shown in cultured postimplantation rat embryos to induce morphological anomalies of the heart, head, neural tube, and forelimb [25].…”
Section: Calcium and Cardiac Precursor Cell Differentiationmentioning
confidence: 59%
“…The dysmorphogenic features predominantly consisted of alteration in the yolk sac and embryonic circulation, enlargement of the cardiac tube or pericardium, craniofacial abnormalities and irregular neural tube. Stein et al [23] examined embryotoxicities of six calcium channel blockers, including NIF and NIT, and suggested that breakdown of yolk sac circulation may drastically affect embryonic development.…”
Section: Discussionmentioning
confidence: 99%
“…Our results indicated that calcium channels were instrumental in controlling preinnervation heartbeats and were functioning at this stage of development (GD 11 to 12) in rat. Stein et al (1990) reported that CCBs affected the yolk sac circulation and embryonic development when rat embryos were cultured with the compounds from GD 9.5 for 48 hr. Our findings were in good agreement with those of Stein's study, although the embryonic ages tested were different.…”
Section: Discussionmentioning
confidence: 99%
“…They also suggested that the digital defects were attributable to maternal and fetal vascular disruptions, which result in a decreased oxygen supply to embryonic/fetal tissue (Danielsson ex al, 1992). Stein et al (1990) found effects of CCBs on embryonic development, particularly on the yolk sac circulation, when rat embryos were cultured with the compounds from Gestation Day (GD) 9.5 for 48 hr. They speculated that the malfunction of the yolk sac circulation might affect embryonic development and that these effects were probably due to the calcium channel blocking properties.…”
mentioning
confidence: 99%